Russian Central Libraries of Border Regions and CIS Countries: Cooperation in the Socio-Cultural Sphere and the Formation of Information Resources - Menshchikova, S. P. (Bibliosfera : zhurnal po bibliotekovedenii͡u︡, bibliografovedenii͡u︡, knigovedenii͡u︡ i informatike, 2025)
CIS border cooperation is important for strengthening good-neighborly relations and further development of the humanitarian space. The article presents the results of the Russian State Library study “Interregional and border cooperation of Russian libraries with the CIS member states. 2010– 2020”. The study’s object is the central universal libraries of border entities of the Commonwealth countries. The purpose of the article is to reflect the results of the study, concerning the formation of information resources and socio-cultural activities. The main research method is a survey, supplemented by the analysis of websites, literature and reports at conferences and round tables. The sources of acquisition of publications in the languages of neighboring countries, forms and methods of working with users have been studied. The state of cooperation in the field of formation of information resources and sociocultural activities, the prevailing areas of interaction have beene determined. Priorities for more effective cooperation have been identified: strengthening ties with regional ethno-cultural societies; ensuring accessibility of documentary collections of national publications, development of electronic information resources; use of modern technologies and forms of work in all areas of cooperation between border libraries; exchange of professional information and experience; active search for sources of funding for work on cross-border cooperation.